y + 7 = -(x - 6) y - 7 = 2(x - 6) y - 7 = -2(x - 6) y + 7 = -2(x + 6)

y + 7 = -(x - 6) y - 7 = 2(x - 6) y - 7 = -2(x - 6) y + 7 = -2(x + 6)

(5, 3), 5/7 (-5, 3), 5/7 (-5, -3), 5/7 (5, -3), 5/7

y - 2 = -(x + 5) y + 2 = (x + 5) y + 2 = -(x - 5) y - 2 = -(x - 5)

4T - T = 125 T = 125/4T 4T = 125/T 4T + T = 125

HELP PLEASE.

Find a formula to find how many kids want to play ball

been doing math for 5 bloody hours and im stumped.

Been trying to solve these 2 but have been struggling with it. Here they are: 1.) (3x)/(2(x+9)) + (x-4)/(x+3) -------------Simplify the expression. 2.)(x-7)/(x^2-8x+15)...

how do i solve this question?i need help

A algebra 2 question from a home school program about counting principals

a company is starting a scholarship fund for it's employees. the company will add to the fund on a yearly basis. each year, it will increase the amount added to the fund the previous year by 10%....

A. 8/17 B. 15/17 C. 17/8 D. 17/15 E. 8/15

g(x)=-5√x+4

The parent function f(x)= √x is reflected across the y axis, vertically stretched by a factor of 5 and translated up 6 units

A carpenter is assigned a job of installing a spa into a pre-existing deck. The dimensions of the deck are 2x wide by (3x + 4) long. The dimensions of the spa are 4x/3 long by x/4 wide. If the...

d varies jointly with the square of w and the cube of p In your equation, use k as the constant of proportionality.

Write the rule for f(x)=x^2 with a vertical compression of 12.

In the equation y = 2x2 - 6x - 8, which of the following is a value of x when y = 0?

I really need an answer ASAP.

√(m/7) +4 =9

Elena B.

GMAT/GRE, SAT/ACT and Advanced Math Expert

Irvine, CA

4.9
(397 ratings)

Cornelia M.

Math Tutor - Specializing in Algebra and Geometry

Lutherville Timonium, MD

5.0
(845 ratings)